Mild attenuation of the pulmonary inflammatory response in a mouse model of hereditary hemochromatosis type 4 - Marques, Oriana; Horvat, Natalie; Altamura, Sandro; Muckenthaler, Martina (Frontiers in physiology, 2021)
The respiratory tract is constantly exposed to pathogens that require iron for proliferation and virulence. Pulmonary iron levels are increased in several lung diseases and associated with increased susceptibility to infections. However, regulation of lung iron homeostasis and its cross talk to pulmonary immune responses are largely unexplored. Here we investigated how increased lung iron levels affect the early pulmonary inflammatory response. We induced acute local pulmonary inflammation via aerosolized LPS in a mouse model of hereditary hemochromatosis type 4 (Slc40a1C326S/C326S), which is hallmarked by systemic and pulmonary iron accumulation, specifically in alveolar macrophages. We show that Slc40a1C326S/C326S mice display a mild attenuation in the LPS-induced pulmonary inflammatory response, with a reduced upregulation of some pro-inflammatory cytokines and chemokines. Despite mildly reduced cytokine levels, there is no short-term impairment in the recruitment of neutrophils into the bronchoalveolar space. These data suggest that increased pulmonary iron levels do not strongly alter the acute inflammatory response of the lung.
Gesehen am 04.02.2021